COMPARATIVE STUDY OF ISLAMIC EDUCATION CURRICULUM INTEGRATION AT SMP AL-ISTIQOMAH AND CHARIYATHAMSUKSA SCHOOL - Mustika Dewi; Siti Khusniyati Sururiyah; Siti Wulan Asih (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to describe and compare the models of Islamic Religious Education (IRE) curriculum integration implemented at SMP Unggulan Al-Istiqomah (Indonesia) and Chariyathamsuksa Foundation School (Thailand) from conceptual, practical, and socio-cultural perspectives. Employing a comparative qualitative approach with a descriptive-analytic design, data were collected through interviews, observations, and document analysis. The findings indicate that SMP Unggulan Al-Istiqomah applies a thematic-holistic integration model that combines the Kurikulum Merdeka with a pesantren-based system. Islamic values are embedded across subjects through the Contextual Teaching and Learning (CTL) approach and character-building activities such as worship routines, Qur’an memorisation, and spiritual reflection. In contrast, Chariyathamsuksa Foundation School adopts a structural-adaptive model with a dual curriculum system that integrates the Thai national curriculum with Islamic Diniyyah education. This model emphasises contextual adaptation within a plural society through bilingual learning and cross-subject integration. The main difference lies in the social context: Indonesia’s Muslim-majority setting enables complete internalisation of Islamic values, while Thailand’s Muslim-minority context requires adaptive strategies under a secular education framework. Despite these differences, both models share the same vision of nurturing students with religious character, intellectual competence, and a balanced integration of faith and knowledge. The study concludes that Islamic curriculum integration should be developed contextually, responsively, and in harmony with each nation’s socio-cultural setting.